Electrochemical stability and degradation of Pd/C and Rh/C catalysts in acidic media - Smiljanić, Milutin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Platinum group metals are key components of electrochemical energy conversion devices due to their superior catalytic and chemical properties. Besides Pt, Pd and Rh attract significant attention in electrocatalysis due to their high activity for different reactions. In addition to activity, the other basic requirement that catalytic material needs to meet is durability under relevant operational conditions. We present here a study on the electrochemical stability of Pd/C and Rh/C catalysts. Following accelerated degradation protocol (ADP) was designed: 0.1 M HClO4 electrolyte, 5000 voltammetric scans at 1 V/s, potential range 0.4–1.4 VRHE. Significant decay of Pd electrochemical surface area (ESA) was paired with substantial Pd dissolution measured by coupling the electrochemical flow cell with ICP-MS (EFC-ICP-MS). Identical location SEM (IL-SEM) revealed that degradation of Pd/C occurs via dissolution of Pd nanoparticles followed by re-deposition. In contrast, only a minor loss of Rh ESA and negligible Rh dissolution occurred under the same conditions, while IL-SEM did not reveal any significant change in the structure of Rh/C. These results are valuable for the proper design of Pd and Rh-based electrocatalytic materials for applications in energy conversion devices.